Central activation of sympathetic neural circuits alters Splenic cytokine gene expression - Ganta, Chanran Kumar (Kansas State University, 2006)
Important bidirectional interactions exist between the central nervous system and the immune system. Neural-immune interactions provide a regulatory system in the body and disturbances in these interactions may lead to disease. Although the sympathetic nervous system is thought to play a key role in mediating neural-immune interactions, central neural mechanisms mediating sympathetic-immune interactions and the effect of centrally-induced alterations in sympathetic nerve discharge on immune function is not known. We tested the hypothesis that central activation of sympathetic neural circuits alters splenic cytokine gene expression. In a separate study, we tested the hypothesis that hypothermia-induced changes in visceral sympathetic nerve discharge (SND) would be attenuated in middle-aged and aged compared with young rats. Previous studies have demonstrated that skin sympathoexcitatory responses to skin cooling are attenuated in aged compared with young subjects, suggesting that advancing age influences sympathetic nerve responsiveness to cooling. The effect of age on sympathetic nerves innervating other targets organs during acute cooling remains unknown. Central activation of splenic SND was produced using three different experimental interventions: increased core body temperature produced by acute heating, intracerebroventricular injection of angiotensin II (ANGII), and decreased core body temperature produced by acute cooling. Changes in gene expression profiles were analyzed using inflammatory cytokine-specific gene-array and further validated using real-time RT-PCR analysis. The following observations were made. 1)Splenic SNDincreased in response to each experimental intervention except in acute cooled young rats where there was a decrease in splenic SND. 2) Splenic cytokine gene expression of pro-inflammatory cytokines (e.g., IL-1β, IL-6, IL-2) and chemokines (GRO1, CXCL2, CCCL2 and, CXCL10) was increased in response to each experimental intervention. 3) Expression of splenic cytokine genes was reduced after splenic-denervation except in acute cooled rats. 4) Progressive hypothermia reduced splenic, renal, and adrenal SND in rats and was generally attenuated in middle-aged and aged rats. These results demonstrate the functional significance of changes in sympathetic nerve activity on splenic immune cell activation and the effect of age on SND responses to core body cooling.
Keywords: Sympathetic Nerve Discharge; Splenic Cytokine Gene Expression; Biology, Animal Physiology (0433); Biology, Neuroscience (0317); Health Sciences, Immunology (0982)